2011
DOI: 10.1002/ange.201008076
|View full text |Cite
|
Sign up to set email alerts
|

Die dreikernigen Kupfer(I)‐Thiolat‐Komplexe [Cu3(NGuaS)3]0/1+ und ihre dimeren Varianten [Cu6(NGuaS)6]1+/2+/3+ mit biomimetischen Redoxeigenschaften

Abstract: Ein redoxaktiver gemischtvalenter Kupfer‐Thiolat‐Komplex entsteht bei der Reaktion von [Cu(MeCN)4]PF6 mit einem CPh3‐Thioether durch ein Zusammenwirken von homo‐ und heterolytischer Spaltung der S‐CPh3‐Bindung. Die Metallatome in dem sechskernigen Kupfer‐Schwefel‐Cluster (siehe Bild) haben im oxidierten Zustand dieselbe mittlere Oxidationsstufe wie im zweikernigen Kupfer‐Thiolat‐Zentrum (CuA) von Cytochrom‐c‐Oxidase und N2O‐Reduktase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 58 publications
0
10
0
3
Order By: Relevance
“…During studies on the influence of polyfunctional ligands containing guanidine‐ and sulfur‐donor functions on the structural and electrochemical properties of copper complexes we were recently able to isolate the disulfide 2′,2′‐(2,2′‐dithiodiphenyl)bis(1,1,3,3‐tetramethylguanidine) (NGuaSSGuaN or (NGuaS‐) 2 ) 3k. 7 Reaction of [Cu(MeCN) 4 ]OTf with a yellow suspension of (NGuaS‐) 2 (ratio 1:1) in acetonitrile resulted in a deep red solution, from which, after filtration and subsequent treatment with diethyl ether, red crystals of [Cu I 2 {(NGuaS‐) 2 } 2 ][OTf] 2 ( 1 [OTf] 2 ; Scheme , route A) separated in the course of one week.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During studies on the influence of polyfunctional ligands containing guanidine‐ and sulfur‐donor functions on the structural and electrochemical properties of copper complexes we were recently able to isolate the disulfide 2′,2′‐(2,2′‐dithiodiphenyl)bis(1,1,3,3‐tetramethylguanidine) (NGuaSSGuaN or (NGuaS‐) 2 ) 3k. 7 Reaction of [Cu(MeCN) 4 ]OTf with a yellow suspension of (NGuaS‐) 2 (ratio 1:1) in acetonitrile resulted in a deep red solution, from which, after filtration and subsequent treatment with diethyl ether, red crystals of [Cu I 2 {(NGuaS‐) 2 } 2 ][OTf] 2 ( 1 [OTf] 2 ; Scheme , route A) separated in the course of one week.…”
Section: Methodsmentioning
confidence: 99%
“…We attribute this behavior to the strong folding of the Cu 2 S 2 diamond, as all mixed‐valence copper complexes known to date have planar frames 2. 3h,k, 11…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex is, as described in Refs. composed of two Cu 3 S 3 rings which are on top of each other and shifted by one atom so that a S atom is on top of a Cu atom. These two rings form a cylindrical hexagon (compare Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[27] It has been shown that type-1 centers can be structurally converted into purple Cu A centers. [29][30][31][32][33][34][35][36][37][38][39][40] The first, though not reversibly reducible, mixed-valent complex has been developed by Tolman and coworkers [41] and theoretically characterized by Solomon et al [42] Duboc and coworkers succeeded in synthesizing a mixed-valent thiolate bridged complex, showing biomimetic functionality. [29][30][31][32][33][34][35][36][37][38][39][40] The first, though not reversibly reducible, mixed-valent complex has been developed by Tolman and coworkers [41] and theoretically characterized by Solomon et al [42] Duboc and coworkers succeeded in synthesizing a mixed-valent thiolate bridged complex, showing biomimetic functionality.…”
Section: Introductionmentioning
confidence: 99%